The ethnoarchaeology of Kalinga basketry when men weave baskets and women make pots - Silvestre, Ramon Eriberto Jader
The earliest indirect evidence of basketry through clay impressions extends back to about 11,000 years (in the Jomon Period), in Egyptian tombs, in early Peruvian sites or the cliff dwellers of the American Southwest. An artifact that has had a long tradition--yet their exact appearance in the archaeological record may never be known with certainty because of factors of preservation. The production of basketry is one of the oldest non-lithic crafts in the world and the evidence of this industry has been continued with little change down to the present time and is very sensitive indicators of cultural chronology. Basketry in contrast to pottery provides a finite number of logical alternatives and the possible combinations are culturally determined to a very high degree. The weaver's relationship with any type of basket is predicated on and conditioned by the fact that all of the weaver's manufacturing choices are physically represented in the finished specimen. It is unfortunate that basketry has not been a major focus of material culture research by archaeologists primarily because of the loss of preservation of baskets in archaeological context. The extant inventory of prehistoric basketry from different parts of the world is but a dim reflection of the original incidence of manufacture. It is unfortunate that basketry has not been a major focus of material culture research by archaeologists and is misunderstood as an artifact class. This ethnoarchaeological study has been initiated to explore the production technology between basket weaving specialists and non-specialists and the distribution of the craft among the Kalinga in the Cordilleras of northern Philippines. The analysis of Kalinga basketry technology and evaluating the economics of the craft is discussed. It hopes to provide a parallel and contrasting understanding of basketry production alongside pottery production extensively researched by the Kalinga Ethnoarchaeology Project. Investigating the initial processes of basketry production, distribution and consumption among the Kalinga should illuminate the understanding of the prehistory of basketry. In the assumption, that the Kalinga is roughly analogous as a neolithic society, popularized in the turn of the century for their headhunting pursuits and a codified custom law.